Detecting Beef Tallow adulteration in Palm Oil with NIR Spectroscopy and Chemometrics Analysis - Mohd Fared Abdul Khir; Marzuki N.Z.S.; Tuhaime N.A.; Basri K.N.; Hussain M.N. (Penerbit UTHM, 2024)
Indexed by WOS/SCOPUS/ERA